Understanding the role of smoking and chronic excess alcohol consumption on reduced caloric intake and the development of sarcopenia. Issue 2 (24th December 2022) - Prokopidis, Konstantinos; Witard, Oliver C.
Abstract: This narrative review provides mechanistic insight into the biological link between smoking and/or chronic excess alcohol consumption, and increased risk of developing sarcopenia. Although the combination of excessive alcohol consumption and smoking is often associated with ectopic adipose deposition, this review is focused on the context of a reduced caloric intake (leading to energy deficit) that also may ensue due to either lifestyle habit. Smoking is a primary cause of periodontitis and chronic obstructive pulmonary disease that both induce swallowing difficulties, inhibit taste and mastication, and are associated with increased risk of muscle atrophy and mitochondrial dysfunction. Smoking may contribute to physical inactivity, energy deficit via reduced caloric intake, and increased systemic inflammation, all of which are factors known to suppress muscle protein synthesis rates. Moreover, chronic excess alcohol consumption may result in gut microbiota dysbiosis and autophagy-induced hyperammonemia, initiating the up-regulation of muscle protein breakdown and down-regulation of muscle protein synthesis via activation of myostatin, AMPK and REDD1, and deactivation of IGF-1. Future research is warranted to explore the link between oral healthcare management and personalised nutrition counselling in light of potential detrimental consequences of chronic smoking on musculoskeletal health outcomes in older adults. Experimental studies should investigate the impact of smoking and chronic excess alcohol consumption on the gut–brain axis, and explore biomarkers of smoking-induced oral disease progression. The implementation of behavioural change interventions and health policies regarding smoking and alcohol intake habits may mitigate the clinical and financial burden of sarcopenia on the healthcare system.